SOCIALLY JUST MINING POLICY IN THE CONTEXT OF REALIZING PEOPLE'S WELFARE - Ninuk Triyanti (Media Inovasi Pendidikan dan Publikasi, 2023)
Mining management is supposed to boost the development and well-being of the people, but excessive exploitation of mining is actually causing environmental damage and suffering to the people. The purpose of this research is to analyze and explain the forms of mining policy that can realize the well-being of the people. This method of research is doctrinal law using library study. The results of the research show that a social justice mining policy can support the realization of people's well-being, which is a mining policy that inspires the value of Pancasila especially please fifth in the framework of the Pancasilla economic system. A social justice mining policy is reflected in legislation that guarantees the principles of justice so that every citizen feels that his or her interests are protected. The existence of a social justice mining policy is a policy that guarantees the principles of justice and that every citizen feels that his or her interests are protected in accordance with human dignity, especially the weak economic communities that are directly affected by the management of mines. The mining policy set out in the Minerba Act already reflects the realization of State sovereignty over national mining but still does not optimally realize a social justice mining policy.